Superbugs an arms race against bacteria - Hall, William (Author of Superbugs) (Harvard University Press, 2018)
Antibiotics are powerful drugs that can prevent and treat infections, but they are becoming less effective as a result of drug resistance. Superbugs describes this growing global threat, the systematic failures that have led to it, and solutions that governments, industries, and public health specialists can adopt.--